2008
DOI: 10.1016/j.jns.2008.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of ocular myasthenia in Korea: A retrospective multicenter analysis of 202 patients

Abstract: Objectives: The aims of this study were to obtain data on the frequency with which Korean patients with autoimmune myasthenia gravis (MG) present solely with ocular disturbances and progress to develop generalized disease and to identify the prognostic factors associated with secondary generalization. Methods: We conducted a retrospective multicenter survey in which a total of 376 adult patients who were newly diagnosed with MG from 2000 through 2005 were reviewed for analysis. Patients with ocular MG at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
84
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 20 publications
21
84
9
Order By: Relevance
“…Sommer et al 6 Previous studies have shown overall conversion rates of OMG to GMG of 50% to 64%. 2,4,12,13 Our series of OMG patients showed a much lower overall conversion rate of 20.9%, consistent with more recent retrospective studies reporting overall conversion rates ranging from 23% to 31%, 6,8,14,15 and this low conversion rate was observed in subjects with or without immunosuppressant therapy. Prior studies have emphasized the possible effect of immunotherapy on conversion rates.…”
Section: Discussionsupporting
confidence: 88%
“…Sommer et al 6 Previous studies have shown overall conversion rates of OMG to GMG of 50% to 64%. 2,4,12,13 Our series of OMG patients showed a much lower overall conversion rate of 20.9%, consistent with more recent retrospective studies reporting overall conversion rates ranging from 23% to 31%, 6,8,14,15 and this low conversion rate was observed in subjects with or without immunosuppressant therapy. Prior studies have emphasized the possible effect of immunotherapy on conversion rates.…”
Section: Discussionsupporting
confidence: 88%
“…This proportion was significantly higher than that shown in other series [9, 10, 12-14]. This apparent worse prognosis observed in our patients could be attributed, in part, to the long follow-up in the present study (mean 8.58 years), making it unlikely that what patients interpreted as ocular MG, later evolved to gMG.…”
Section: Discussioncontrasting
confidence: 82%
“…Myasthenia gravis (MG) is a prototypical antibody-mediated autoimmune disease characterized by production of autoantibodies against the skeletal muscle acetylcholine receptor (AChR) at the neuromuscular junction (NMJ) [1]. Ocular MG (OMG) is the most common initial presentation of MG, occurring in about 85% of MG patients.…”
Section: Introductionmentioning
confidence: 99%